Eyes on the ground and eyes in the sky: Security narratives, participatory visual methods and knowledge production in 'danger zones'. (December 2022) - Chonka, Peter; Edle Ali, Abdirahman; Stuvøy, Kirsti
This article reflects on the use of narrative interviews alongside participatory and remote-access visual methods to produce knowledge on and in conflict-affected settings. It details our iterative and reactive experiences of navigating transnational academic, policy and humanitarian networks to attempt to undertake ethical research on the security experiences of displaced people in Somali cities and facilitate their engagement with policymakers. We explore tensions in the combined use of increasingly accessible digital tools (camera-equipped smartphones and open-access satellite imagery) in facilitating a participatory, narrative-based approach to security research while also mitigating access limitations to research sites. We argue that a holistic and reflexive approach to everyday security within a technologically mediated data-collection process – for both researchers and research participants – not only is important for negotiations around ethical fieldwork, but also can be generative of findings about the research site itself. Methods are not brought into a context and deployed by researchers in ways that are fully under their control. In the case explored here, how the researchers and research participants engaged in dialogue about various methods, reflected their connections within networks of knowledge production dominated by humanitarian donors/partners, while also highlighting important aspects of displaced people's everyday experiences of (in)security and marginalization in Somali cities.